Analisis Skala Ekonomis Pada Industri Kriya Kayu Di Kabupaten Badung - Periadnyani, Dewa Ayu; Saskara, Ida Ayu Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2015)
The growth of the textile sector of the apparel industry in Indonesia will greatly been affected by the business scale or production scale, the larger the business scale or production scale tends to indicate the level of efficiency. This research has the purpose of (1) the influence of labor and capital, either simultaneously or partially to the production of wood crafts, (2) determine the economic scale wood craft industry in Badung, (3) determine the nature of the industrial production of wood craft in Badung intensive work or capital intensive. Study choose Badung, by examining the wood craft industry with a population of 539 business units that are scattered in the district of South Kuta, Kuta, North Kuta, Mengwi, Abiansemal and evening with multiple linear regression analysis technique. Samples taken as many as 84 drawn at random by using Slovin formula. Results prove labor and capital have a significant effect simultaneously on wood craft industry with a value Fhitung (98.844)> F table (3.92). Labor and capital has positive effect partially on wood craft industry. Wood craft industry economies of scale that are in decreasing returns of scale. Production of wooden craft industry in Badung are labor intensive
Keywords: Labor; Capital and Production Industry